Magnetic resonance T1-mapping quantitatively assesses the severity of thyroid destruction in patients with autoimmune thyroiditis - Liu, Jia; Chang, Xiaona; Wang, Qiu; Ding, Xiaoyu; Jiang, Tao; Wang, Guang (Frontiers in Endocrinology, 2022)
Objective Autoimmune thyroiditis (AIT) is a common organ-specific autoimmune disease. Longitudinal relaxation time mapping (T1-mapping) analyzed by magnetic resonance imaging is a new method for evaluating inflammation or fibrosis. This study aimed to investigate the relationship between thyroid T1-mapping value and degree of intrathyroidal inflammation and destruction in euthyroid AIT patients. Methods This case-control study recruited 28 drug-naïve AIT patients and 18 healthy controls. Thyroid specimens were collected for assessing the mRNA expression of inflammatory factors and histopathologic examination. T1-mapping values were measured using a modified look-locker inversion-recovery sequence in all participants. Results The positive rate of pathological diagnosed AIT was only 83.3% in the AIT group diagnosed by positive TPOAb and/or TgAb and typical ultrasonic manifestations, while 7.1% of the control group was diagnosed as AIT by pathological manifestations. Receiver operating characteristic curve analysis revealed a very high diagnostic value of thyroid T1-mapping values for pathological diagnosed AIT (area under the curve was 0.950, 95%CI: 0.843 – 0.993, P < 0.001). In the patients with pathological diagnosed AIT, thyroid T1-mapping values were significantly associated with the mRNA expression of INF-γ (r = 0.343, P < 0.05), TNF-α (r = 0.352, P < 0.01), and IL-1β (r = 0.673, P < 0.01) in thyroid tissues. Moreover, histopathologic examination showed that thyroid T1-mapping values can properly reflect the degree of thyroid destruction in AIT patients. Conclusions Thyroid T1-mapping values had a very high diagnostic value for AIT. In euthyroid AIT patients, thyroid T1-mapping values better reflect degree of intrathyroidal inflammation and destruction.